Valvular Heart Disease and Pregnancy in the Delivery Room at Yalgado Ouedraogo University Hospital about 12 Cases - Jonas Kologo, Koudougou; Rosario Christian Millogo, Georges; Salissou Seck Mbaye, Mbaye; Aristide Yaméogo, Relwendé; Adoko, Hermann; Mandi, Germain; Bernard Ouedraogo, W; Zingué, Adolphe; Thiam/Tall, Anna; K. Samadoulougou, André (Journal of Hypertension and Cardiology, 2022)
This series summarizes 12 pregnancies complicated by valvular heart disease, focusing on intrapartum management, anesthesia choices, and maternal–fetal outcomes in a resource‑limited setting.
Keywords: Heart; congenital; pregnancy